ORGANIZATIONAL-PEDAGOGICAL APPROACHES IN DEVELOPING DIGITAL COMPETENCE OF FUTURE TEACHERS - Turdaliyev Sodikjon Muminjonovich (Modern American Journals, 2025)
The article justifies the need to use modern digital technologies and information and communication tools in teacher training in the conditions of increasing information volume and limited educational time. The development of digital competence is emphasized as a key area, especially in the professional training of future teachers. The article analyzes the importance of the course "Application of Information Technologies in Professional Activities", pedagogical conditions, organizational and methodological foundations, as well as approaches to the development of digital competence - competency-based, modular, integrative, digital environment-based, differential and digital pedagogical design approaches.
Keywords: Digital competence, future teachers, information technologies, digital education, digital literacy, pedagogical approaches.